Detection of biological activity and inhibitory effect of the extract of Plantago lanceolata L. leaves on the bacteria that cause skin inflammation and the role of extract in deep wound repair - Ekhlas Gumar Abed; Mustafa Muthana Abdalrazak; Atlal Naje Manjy (Journal of Madenat Alelem University College, 2019)
The biological activity and inhibitory effect of the young leaf extract of the plant Plantago lanceolata was detected By using a modified method inestate of mechanized method for digestion of young leaves and cold extraction of juice and then preparation of gradient concentrations of the plant extract and study its effect on the growth of skin pathogenic bacteria (Staphylococcus aureus , Streptococcus pneumuonia , Esherichia coli and Pseudomonus aeruginosa ) by measuring the diameter of the growth inhibiting region .The diameter of the inhibition zone for Pseudomonus aeruginosa at the concentration of 50 mg / ml were (12,15,10,11 mm), respectively, at 100 mg / ml, the diameter of the inhibition zone were (20, 26,13,15 mm) while the diameter of inhibition zone at 200 mg/ml were )17,20,30,32 mm( respectively, the diameter of the inhibition zone were ( 35,38,22,18 mm). The extracted pH was measured and ranged between 5.4 - 5.6 . The mineral contents was determind and compared with two life periods of plant leaves young leaves and mature leaves in young leaves were (iron 1.26 ppm, calcium 12.5ppm, potassium 34.2ppm, zinc 0.198 ppm) in matuere leaves were (iron 0.125ppm, calcium 5.11 ppm, potassium 1.1 g/L Zinc 3.50 ppm, copper 0.31ppm).